Revenue and Cost Analysis for Unhealthy Commodity (Tobacco Products): Comparative Study among Indonesia and some ASEAN Countries (Unnes Journal of Public Health, 2020)
This research aims to analyze aspects of demand, costs and benefits of tobacco products in Indonesia and several other ASEAN countries (such as: Brunei, Cambodia, Laos, Malaysia, Philippines, Singapore, Thailand and Vietnam). The research approach used is descriptive comparative analysis and quantitative analysis to examine the relationship between demand factors and cost factors with explanatory variables, namely: price level, amount of excise, government revenue and cross-country specific factors. The descriptive approach is carried out by analyzing secondary data from the results of previous research studies. While the quantitative approach is done using standard regression analysis and instrument variable approach. The results of the study indicate that among ASEAN countries, Indonesia is known as the country with the highest rate of smoking prevalence for adult men (67 percent). The results showed that a one percent price increase would reduce the prevalence to around 0.27 percent (significance at 1%). Meanwhile the increase in prevalence will increase costs by an average of 14.71 million US dollars (significance at 5%). That is, the higher the state revenue from cigarette excise, the higher the costs to be borne. These results further strengthen the urgency of tobacco control in Indonesia.